Risk of nontyphoidal Salmonella bacteraemia in African children is modified by STAT4 - James J. Gilchrist (Nature Portfolio, 2018)
Nontyphoidal Salmonella (NTS) is a major cause of bacteraemia in children and HIV-infected adults in Africa. Here, Gilchrist et al. conduct a genome-wide association study and show that genetic variation in STAT4 is a determinant of NTS in Kenyan and Malawian children.